Distributed Skin Lesion Analysis Across Decentralised Data Sources...Medical Informatics Europe, Public Health and Informatics Conference (Virtual), 29-31 May, 2021. - MOU, Yongli; WELTEN, Sascha; JABERANSARY, Mehrshad; UCER YEDIEL, Yeliz; KIRSTEN, Toralf; DECKER, Stefan; BEYAN, Oya (Studies in Health Technology & Informatics, 2021)
Skin cancer has become the most common cancer type. Research has applied image processing and analysis tools to support and improve the diagnose process. Conventional procedures usually centralise data from various data sources to a single location and execute the analysis tasks on central servers. However, centralisation of medical data does not often comply with local data protection regulations due to its sensitive nature and the loss of sovereignty if data providers allow unlimited access to the data. The Personal Health Train (PHT) is a Distributed Analytics (DA) infrastructure bringing the algorithms to the data instead of vice versa. By following this paradigm shift, it proposes a solution for persistent privacy-related challenges. In this work, we present a feasibility study, which demonstrates the capability of the PHT to perform statistical analyses and Machine Learning on skin lesion data distributed among three Germany-wide data providers.